Projeto e desenvolvimento de um condicionador unificado de qualidade de energia - Camilo Lelis Mota de Paula (2019)
This work presents the design and development of a 7.6kVA Unified Power Quality Conditioner, widely known by the acronym UPQC. It consists of a project capable of compensating power quality problems by combining the characteristics of a series and shunt power active filter. Thus, it is able to correct the harmonic voltage and current distortions, in addition to compensating reactive and regulate the voltage supplied to the load. The control of the system will be based on synchronous and stationary references frame, allowing a comparison between them, where the modeling procedures of active power filters will be addressed, in addition to the design and adjustment of controllers. For the synthesis of harmonic components, which escape from the passage range of the controller, resonant controllers will be used, which apply an infinite gain in the selected resonance frequency, in such a way to eliminate the error in permanent regime. In addition, other details of UPQC implementation will be presented, such as for example, grid synchronization technique, project sizing, modulation technique used, grid connection filter sizing, commissioning details, initial loading of the DC bus and protections implemented. Besides discussions and conclusions related to the results obtained through the UPQC prototype, such as responses of the implemented control systems, reactive power injection, harmonic current injection, voltage restoration, unbalanced voltage synthesis, and synthesis of harmonic voltage components. The design and development of the UPQC will ensure an operational prototype, with power up to 7.6kVA, maximum current of 20Arms, maximum switching frequency of 15kHz, direct current bus capable of operating up to 750V and can be applied to tests of linear and non-linear loads. This allows the validation of theories and computational simulations with an exact perspective of the real difficulties of implementation.